Exports, Growth and Causality: An Application of Co-integration and Error-correction Modelling (The Pakistan Development Review, 1995)
The relationship between export expansion and economic growth has been examined extensively during the last two decades in the context of the suitability of the alternative development strategies. The decade of the 1970s witnessed an emerging consensus in favour of export promotion as development strategy. Such a consensus was based on the following facts. First, higher export earnings working through alleviating foreign exchange constraints may enhance the ability of a developing country to import more industrial raw materials and capital goods, which, in turn, may expand its productive capacity. Secondly, the competition in export markets abroad may lead to the exploitation of economies of scale, greater capacity utilisation, efficient resource allocation, and an acceleration of technical progress in production. Thirdly, given the theoretical arguments mentioned above, the observed strong correlation between exports and economic growth was interpreted as empirical evidence in favour of export promotion as a development strategy. The empirical evidence in favour of export promotion rests on the general approach where real growth is regressed on contemporaneous real export, growth and the significance of the export growth coefficient supports the proposition that export growth causes output growth. Balassa (1978); Feder (1982); Fosu (1990); Kavoussi (1984); Tyler (1981) and Ram (1985) have followed such an approach.1 Khan and Saqib (1993), on the other hand, examined the relationship between exports and economic growth by constructing a simultaneous equation model comprising equations for exports and economic growth. They found a strong association between export performance and GDP growth for Pakistan, and that more than 90 percent of the contribution of exports on economic growth was indirect in nature.